Numerical and Experimental Evaluation of Ceramic Honeycombs for Thermal Energy Storage. Issue 2 (3rd April 2017) - Srikanth, Ojasve; Khivsara, Sagar D.; Aswathi, R.; Madhusoodana, C. D.; Nath Das, Rathindra; Srinivasan, Vinod; Dutta, Pradip
ABSTRACT: Thermal energy storage at high temperature is a challenging research area with typical applications like regenerative heating in steel production plants and auxiliary energy source in solar thermal plants. Honeycomb structures made of ceramics are used as high temperature thermal energy storage units because of their large heat transfer surface area per unit volume, large thermal capacity and good thermal shock resistance. The material properties and geometric parameters of these units determine the storage capacity and heat addition/retrieval rate. A thorough understanding of the thermal response of storage unit at different process conditions is crucial for designing the system. In this work, new compositions of mullite and chromite based ceramic honeycombs were developed for high temperature thermal storage application. An experiment was designed to evaluate the performance of the ceramic honeycomb in the temperature range of 773-1273 K by studying the storing and discharging characteristics in cyclic mode. Numerical studies using ANSYS Fluent have been presented to predict the effect of honeycomb design, material properties and flow rates on thermal energy storage and heat transfer characteristics. This data are used to validate the experimental results and for designing an optimum thermal energy storage system. GRAPHICAL ABSTRACT: